2022
DOI: 10.1155/2022/4671719
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cholera Outbreak and Summary of the Preparedness and Response Activities in Addis Ababa, Ethiopia, 2016

Abstract: Background. Cholera is a major public health problem in Ethiopia. This study aimed to generate evidence to better understand the epidemiology of cholera as well as chronicle the city administration’s emergency management efforts during the Addis Ababa cholera outbreak in 2016. Method. A descriptive analysis was performed using the cholera outbreak data collected from June 8 to October 31, 2016. A case was defined as a patient aged 5 years or older who develops acute watery diarrhea with or without vomiting. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This is in agreement with the previous studies done in Nigeria, South Africa, Ethiopia, and India. 6,38,39 However, the reverse was the case in earlier studies carried out in Nigeria, some other West African countries (Benin, Burkina Faso, Cameroon, Mali, Niger, Togo), Pakistan and Malta. 25,28,29,31,37,41,44 The cases of acute watery diarrhoea can be classified into two distinct waves; with a greater frequency of cases and deaths occurring in the second wave following the diagnosis of cholera as opposed to a less eventful first wave with a low attack rate but a high case fatality rate than most of the previous studies.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This is in agreement with the previous studies done in Nigeria, South Africa, Ethiopia, and India. 6,38,39 However, the reverse was the case in earlier studies carried out in Nigeria, some other West African countries (Benin, Burkina Faso, Cameroon, Mali, Niger, Togo), Pakistan and Malta. 25,28,29,31,37,41,44 The cases of acute watery diarrhoea can be classified into two distinct waves; with a greater frequency of cases and deaths occurring in the second wave following the diagnosis of cholera as opposed to a less eventful first wave with a low attack rate but a high case fatality rate than most of the previous studies.…”
Section: Discussionmentioning
confidence: 84%
“…6,31,35,36 Contrarily, studies carried out in Nigeria, Ethiopia, Bangladesh, and Malta revealed that cases of acute watery diarrhoea were observed more among patients in their middle adolescence, early adulthood and older age groups as opposed to younger children. 25,28,[37][38][39][40][41] Additionally, a greater proportion of all line-listed patients were slightly more males than females. This is in agreement with the previous studies done in Nigeria, South Africa, Ethiopia, and India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 200 serogroups of the bacteria have been identified so far, and cholera outbreaks mainly occur during the hot months of summer elicited by the O1 or O139 biotype ( Ali et al 2015 ; Ramazanzadeh et al 2015 ). Severe watery diarrhea, known as “rice-watery” stool, odorless or of a mild fishy smell, with or without vomiting, are the major symptoms of the disease ( Harris et al 2012 ; Endris et al 2022 ). Among different age groups, children below five years old are the most vulnerable to cholera compared to adults or the elderly ( Deen et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cholera is considered a global health issue, and it has affected most parts of the world since the early of the nineteenth century ( Harris et al 2012 ). A majority (~ 99%) of cholera cases have been recorded in Africa and Southern Asia ( Deen et al 2008 ; Endris et al 2022 ). In 2006, more than two million cholera cases with 6,311 deaths were recorded in 52 countries ( WHO 2007a ).…”
Section: Introductionmentioning
confidence: 99%